N-Acetylcysteine as Modulator of the Essential Trace Elements Copper and Zinc - Theresa Wolfram; Maria Schwarz; Michaela Reuß; Kristina Lossow; Mario Ost; Susanne Klaus; Tanja Schwerdtle; Anna P. Kipp (MDPI AG, 2020)
N-acetylcysteine (NAC) is a frequently prescribed drug and known for its metal chelating capability. However, to date it is not well characterized whether NAC intake affects the homeostasis of essential trace elements. As a precursor of glutathione (GSH), NAC also has the potential to modulate the cellular redox homeostasis. Thus, we aimed to analyze effects of acute and chronic NAC treatment on the homeostasis of copper (Cu) and zinc (Zn) and on the activity of the redox-sensitive transcription factor Nrf2. Cells were exposed to 1 mM NAC and were co-treated with 50 μM Cu or Zn. We showed that NAC treatment reduced the cellular concentration of Zn and Cu. In addition, NAC inhibited the Zn-induced Nrf2 activation and limited the concomitant upregulation of cellular GSH concentrations. In contrast, mice chronically received NAC via drinking water (1 g NAC/100 mL). Cu and Zn concentrations were decreased in liver and spleen. In the duodenum, NQO1, TXNRD, and SOD activities were upregulated by NAC. All of them can be induced by Nrf2, thus indicating a putative Nrf2 activation. Overall, NAC modulates the homeostasis of Cu and Zn both in vitro and in vivo and accordingly affects the cellular redox balance.